The go-between - Chambers, Veronica (New York : Delacorte Press, 2017)
Both of sixteen-year-old Cammi's parents are stars in Mexico, but everything changes when her mother accepts a role in an American sitcom.
A Junior Library Guild selection (JLG.)
Keywords: Celebrities -- Fiction; Immigrants -- Fiction; High schools -- Fiction; Schools -- Fiction; Social classes -- Fiction; Families -- California -- Los Angeles -- Fiction; Mexican Americans -- California -- Fiction; Young adult fiction; Celebrities -- Fiction; Immigrants -- Fiction; High schools -- Fiction; Schools -- Fiction; Social classes -- Fiction; Family life -- California -- Los Angeles -- Fiction; Mexican Americans -- Fiction; Mexican Americans -- Fiction